A real estate portfolio management risk assessment framework for nonlisted real estate funds in India. Issue 1 (23rd October 2020) - Gupta, Ashish; Newell, Graeme
Abstract : Purpose: This study provides an extensive risk assessment framework for nonlisted real estate funds' (NREFs) portfolio management in India across their life cycle; that is, the investment stage, the monitoring stage and the exit stage in an emerging market context. The study of risk across these three stages is a new addition to the literature and assumes importance in the context of real estate portfolio management for NREFs in the emerging markets (e.g. India), which are predominantly an opportunistic investment play. Design/methodology/approach: The risk assessment framework is built on the multiactor/multicriteria risk priorities, using analytical hierarchy process (AHP), obtained from 35 experts in four real estate fund management professional groups; namely, investors/fund managers, valuers, consultants and international developers. Findings: The results demonstrate that the real estate portfolio management risk priorities change across the three life cycle stages of the fund. At the investment stage, specific risks are most critical; at the monitoring stage, it is important to concentrate on all three risks – specific, systematic and management risks; and at the exit stage, systematic risk plays a crucial role. Real estate portfolio management risk evaluation at the subfactor level shows that investee/partner and location selection needs to be critically evaluated at the time of the investment; project execution and quality of development must be monitored during the construction/monitoring period; and repatriation of the funds, currency volatility and exit risk (resale) are critical at the exit stage of the fund. Practical implications: The understanding of the real estate portfolio management risk transformation across the life cycle stages is crucial for NREF managers for risk minimization, transfer and mitigation strategy formulation in their real estate portfolios. Unlike previous research that evaluates investment risk, this study breaks the NREF's risks into the investment, monitoring and exit stages. The key risk factors for each stage depend on the NREF's real estate activities for that stage. These activities, in turn, give rise to a typical risk profile for that stage. The findings are crucial for the various stakeholders of real estate fund management and policymakers in an emerging market context; particularly India, one of the fastest growing major economies in the world. Originality/value: This risk assessment framework for simultaneously assessing risk across the three life cycle stages of NREFs is a new addition to the literature.